Severe malaria in children in Yemen: two site observational study. Issue 7573 (19th October 2006) - Al-Taiar, Abdullah; Jaffar, Shabbar; Assabri, Ali; Al-Habori, Molham; Azazy, Ahmed; Al-Mahdi, Nagiba; Ameen, Khaled; Greenwood, Brian M; Whitty, Christopher J M
Abstract: Objectives To assess the burden of malaria on health services, describe the clinical presentation of severe malaria in children, and identify factors associated with mortality by means of a prospective observational study. Setting Two public hospitals in Taiz (mountain hinterland) and Hodeidah (coastal plain), Yemen. Participants Children aged 6 months to 10 years. Results Of 12 301 paediatric admissions, 2071 (17%) were for suspected severe malaria. The proportion of such admissions varied according to the season (from 1% to 40%). Falciparum malaria was confirmed in 1332 children; 808 had severe disease as defined by the World Health Organization. Main presentations were respiratory distress (322/808, 40%), severe anaemia (291/800, 37%), and cerebral malaria (60/808, 8%). Twenty two of 26 children who died had a neurological presentation. No deaths occurred in children with severe anaemia but no other signs of severity. In multivariate analysis, a Blantyre coma score ≤ 2, history of fits, female sex, and hyperlactataemia predicted mortality; severe anaemia, respiratory distress, and hyperparasitaemia were not significant predictors of mortality. Conclusions Severe malaria puts a high burden on health services in Yemen. Although presentation is similar to African series, some important differences exist. Case fatality is higher in girls.